Amorphous cellulose feed supplement alters the broiler caecal microbiome. (7th May 2019) - De Maesschalck, Celine; Eeckhaut, Venessa; Maertens, Luc; De Lange, Loek; Marchal, Leon; Daube, Georges; Dewulf, Jeroen; Haesebrouck, Freddy; Ducatelle, Richard; Taminau, Bernard; Van Immerseel, Filip
ABSTRACT: The grains that form the basis of most commercial chicken diets are rich in cellulose, an unbranched β-1, 4-linked D-glucopyranose polymer, used as a structural molecule in plants. Although it is a predominant polysaccharide in cereal hulls, it is considered an inert non-fermentable fiber. The aim of the current study was to analyze the effect of in-feed supplementation of cellulose on the gut microbiota composition of broilers. Administration of cellulose to chickens, on top of a wheat-based diet, changed the caecal microbiota composition, as determined using pyrosequencing of the 16S rRNA gene. At day 26, a significantly ( P < 0.01) higher relative abundance of the Alistipes genus was observed in the caeca of broilers fed the cellulose-supplemented diet, compared to animals fed the control diet. An in vitro batch fermentation assay showed a significant ( P < 0.01) growth stimulation of Alistipes finegoldii in the presence of cellulose. In conclusion, in-feed supplementation of cellulose alters the microbiota composition at the level of the phylum Bacteroidetes, specifically the Alistipes genus. This suggests that cellulose is not essentially inert but can alter the gut micro-environment.